2022
DOI: 10.1371/journal.pone.0275109
|View full text |Cite
|
Sign up to set email alerts
|

Developing an active lifestyle for children considering the Saudi vision 2030: The family’s point of view

Abstract: Motivating children to lead a healthy and active lifestyle is a family mission and a responsibility shared by society. This study is important in developing the family’s role in promoting children’s active lifestyle. This study aims to develop the role of the family in promoting an active lifestyle for children in light of the Saudi vision 2030. The sample included 405 parents who filled out an online survey about their children aged 3–12 years. The results show families’ lack of interest in applying the WHO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…In terms of physical activity, the study found inadequate physical activity as a daily routine, specifically among older children (3-6 years) (p-value = 0.017). This is similar to a recent survey in Saudi Arabia, which indicates a worrying lack of knowledge and enthusiasm among parents about the right amounts of physical activity for their kids [ 28 ]. There is an urgent need for additional initiatives to counteract Saudis’ rising propensity for inactivity and unhealthy living.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of physical activity, the study found inadequate physical activity as a daily routine, specifically among older children (3-6 years) (p-value = 0.017). This is similar to a recent survey in Saudi Arabia, which indicates a worrying lack of knowledge and enthusiasm among parents about the right amounts of physical activity for their kids [ 28 ]. There is an urgent need for additional initiatives to counteract Saudis’ rising propensity for inactivity and unhealthy living.…”
Section: Discussionsupporting
confidence: 88%
“…The mothers were predominantly well educated as 58.7% of them have a doctoral degree. However, Rakha et al (2022) found widespread parental reluctance to adopt overarching health guidelines associated with weight and BMI in households with children age 3-12. Interestingly, in yet another study conducted by Mortada et al (2017) among PNU Saudi (not Saudi female employees) obtained the same results even when the sample was heterogeneous, as their educational level was distributed as the following: 15.4% high school degree, 50% bachelor's degree, 14.6% master's degree, and 20% doctoral degree (Mortada et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we sought to examine the association between parenting style and BMI in Saudi Arabia. The rationale for this examination is the increasingly high prevalence of overweight and obesity (13.4% and 18.2 respectively in 2019) among Saudi children who aged from 6 to 11 years old and in light of the 'Saudi Vision 2030' initiative (Al-Hussaini et al 2019;Rakha et al 2022). The same study reported that overweight and obesity prevalence were higher among girls than boys.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Stimulasi fisik dapat memfasilitasi beberapa aspek dari perkembangan motorik.Stimulasi fisik sangat penting untuk perolehan progresif keterampilan mental dan motorik yang menentukan perkembangan anak (Gagen & Getchell, 2006;Leung, 2020). Selain itu, ada kebutuhan untuk mengembangkan media dan kesadaran bagi keluarga untuk mencapai tujuan yang diinginkan dalam mengembangkan gaya hidup aktif untuk anak-anak (Pethkar, 2018;Rakha et al, 2022). Gaya hidup aktif Pulung Riyanto / Keterampilan Motorik Kasar Anak Prasekolah: Analisis Program Intervensi Motorik selama masa kanak-kanak bermanfaat bagi kesehatan fisik, kognitif, dan mental (Hammersley et al, 2022).…”
Section: Pendahuluanunclassified